VITALITAS BAHASA MADURA : TINJAUAN AWAL DALAM PEMERTAHANAN BAHASA IBU PENDUDUK MADURA DI SURABAYA - Rachma, Evi Pebri Ila; Mohammad Halili ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2024)
Surabaya, as a multi-ethnic city, was chosen as the research area. Javanese is the language widely used, and Madurese is the minority language in Surabaya. Madurese is part of the multilingualism that exists in Surabaya. This research focuses on the domains affecting Madurese language communication and vitality in Surabaya. This is a quantitative descriptive study using questionnaire instruments. The research results show that the vitality of the Madurese language is not in a safe scale, but rather in a vulnerable scale. Madurese language usage is low in domains such as population mobility, language transmission between generations, use in communication with government, use in education, bilingualism, religion, and language documentation. Keywords : language vitality, Madurese language, language maintenance.